Organizational Identification and User Responses to Online Organization Criticism. Issue 2 (3rd March 2020) - Nguyen, Quynh N.; Sidorova, Anna
ABSTRACT: As organizations manage their reputations on social media, the role of individual stakeholders in responding to online criticism about the organization becomes increasingly important. Building on the organizational identification literature, this study examines the role of organizational identification and organizational identity orientation in motivating stakeholder responses to organization-directed criticism on social media. Analysis of survey data reveals that organizational identification is positively related to individuals' propensity to respond to negative content and that individuals with stronger organizational identification are likely to respond in a more cooperative manner. Organizational identity orientation moderates the relationship. The study's implications for research and practice are discussed.